Analysis of Damage to the Axle Counter of the ZP D 43 Module at the Maros Station Crossing - Mujahid, Ghozy Akram; Hakim, Mohamad Lukman; Nugraha, Nathanael Tegar Putra; Darmawan, Arief (International Journal of Advanced Multidisciplinary, 2025)
This study analyzed the damage to the Axle Counter Module ZP D 43 at the Maros Station crossing. The ZP D 43 module functions to detect the presence of the train, but it was found to be disrupted due to lightning strikes and a poor grounding system, which caused fatal damage to the module and counting head. The research method uses a qualitative approach through observation, technician interviews, as well as SWOT and TWOS analysis. The results of the SWOT and TOWS analyses show the need to improve system protection and grounding improvements to improve operational reliability. These findings provide strategic recommendations to improve the safety and efficiency of train travel in the Makassar–Parepare Railway Project.